Highly polar solvent-induced disproportionation of a cationic Pt(ii)–diimine complex containing an o-semiquinonato. Issue 12 (26th February 2016) - Yamada, Shota; Matsumoto, Takeshi; Wakizaka, Masanori; Chang, Ho-Chol
Abstract : The unprecedented disproportionation of [Pt II (3, 5-DTBSQ)(DTBbpy)] + PF6 − in highly polar solvents, DMSO and DMF, was elucidated for the first time. Abstract : Chemical one-electron oxidation of [Pt II (3, 5-DTBCat)(DTBbpy)] (1 ) (3, 5-DTBCat = 3, 5-di- tert -butyl catecholato, DTBbpy = 4, 4′-di- tert -butyl-2, 2′-bipyridine) afforded the corresponding paramagnetic complex, [Pt II (3, 5-DTBSQ)(DTBbpy)] + PF6 − (1 (PF6 )), as a result of ligand-centred oxidation. While complex1 is relatively stable in common organic solvents, the present study demonstrates that cationic [1 ] + is subject to an unprecedented solvent-induced disproportionation in highly polar solvents such as DMSO and DMF, which results in the formation of1 and a free benzoquinone.